The Imagological Contexts of Antoni Malczewski's "Maria" - Брацка, Марія Валентинівна; Садовий, Микита (Київського національного університету імені Тараса Шевченка, 2025)
This work provides a descriptive and comparative analysis of the images of Cossacks and Tatars in Antoni Malczewski’s poem “Maria”, examined within the context of imagology and inter-ethnic relations. The poem delineates a clear dichotomy between Good, embodied by the Poles and Cossacks, and Evil, represented by the Tatars. The image of the Cossack is portrayed as multifaceted and complex: he is a harmonious blend of “wildness” and “obedience”, lives in unity with nature, and serves as a loyal messenger, a reliable guide, and a brave warrior. He functions as an “intermediate link” between “civilization” (the Poles) and “barbarism.” In contrast, the Tatars are depicted as a faceless, cruel, and treacherous horde, symbolizing absolute evil, chaos, and a destructive force of nature. This contrast is further deepened by the analysis of their combat tactics: the noble and direct fighting style of the Poles is set against the cunning maneuvers and encirclement tactics of the Tatars. Thus, in the poem, the Cossacks emerge as allies of civilization in its struggle against barbarism.

Стаття є описовим та компаративним аналізом образів козаків та татар у поемі Антонія Мальчевського «Марія» в контексті імагології та міжетнічних стосунків. У поемі простежується чітка дихотомія Добра, яке уособлюють поляки і козаки, та Зла, представленого татарами. Образ козака розглядається як багатогранний та складний: він є гармонійним поєднанням «дикості» й «слухняності», перебуває у єдності з природою, виступає як вірний посланець, надійний провідник і хоробрий воїн. Він діє як «проміжна ланка» між «цивілізацією» (поляками) та «варварством». На противагу цьому, татари зображені як безлика, жорстока та підступна орда, що символізує абсолютне зло, хаос та руйнівну природну стихію. Цей контраст поглиблюється через аналіз бойових тактик: шляхетний і прямолінійний бій поляків протистоїть хитрим маневрам і тактиці оточення татар. Таким чином, козаки в поемі стають союзниками цивілізації у її боротьбі проти варварства.
Імагологічні контексти «Марії» Антонія Мальчевського
Keywords: Antoni Malczewski’s “Maria”; imagology; image of the Cossack; image of the Tatar; civilization and barbarism; Антоній Мальчевський; «Марія»; імагологія; образ козака; образ польського шляхтича; образ татарина; цивілізація і варварство